1988
DOI: 10.1093/oxfordjournals.aje.a114877
|View full text |Cite
|
Sign up to set email alerts
|

Cryptorchism, Orchiopexy, and the Risk of Testicular Cancer

Abstract: Adult white male residents of 13 counties of western Washington State in whom germ cell testicular cancer was diagnosed between 1977 and 1983 (n = 333) were interviewed by telephone regarding their history of cryptorchism and its treatment. The same interview was given to a sample of 675 men selected from the population of these counties by dialing telephone numbers at random. Men who reported a history of cryptorchism were 5.9 times (95 per cent confidence interval 3.4-10.2) more likely than men without such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 0 publications
1
29
1
4
Order By: Relevance
“…Among the authors who have examined risks separately, Morrison (1976), Stone et al (1991) and Prener et al (1996) found a significantly stronger association with seminoma, Morrison (1976) for example reported OR of 15.6 for pure seminoma compared with 5.3 for non-seminoma, and Prener et al (1996) reported OR of 7.3 and 3.6 respectively. Henderson et al (1979), Moss et al (1986), Swerdlow et al (1987), Strader et al (1988), Haughey et al (1989), Gallagher et al (1995) and reported similar risks associated with undescended testis in the two histological groups, although where separate OR were presented, they were consistently higher for seminomas than other tumours (Moss et al, 1986;Swerdlow et al, 1987;Strader et al, 1988;. In a case-control study only of pure seminoma tumours (Coldman et al, 1982) the OR associated with undescended testis was 17.1.…”
Section: Discussionmentioning
confidence: 87%
“…Among the authors who have examined risks separately, Morrison (1976), Stone et al (1991) and Prener et al (1996) found a significantly stronger association with seminoma, Morrison (1976) for example reported OR of 15.6 for pure seminoma compared with 5.3 for non-seminoma, and Prener et al (1996) reported OR of 7.3 and 3.6 respectively. Henderson et al (1979), Moss et al (1986), Swerdlow et al (1987), Strader et al (1988), Haughey et al (1989), Gallagher et al (1995) and reported similar risks associated with undescended testis in the two histological groups, although where separate OR were presented, they were consistently higher for seminomas than other tumours (Moss et al, 1986;Swerdlow et al, 1987;Strader et al, 1988;. In a case-control study only of pure seminoma tumours (Coldman et al, 1982) the OR associated with undescended testis was 17.1.…”
Section: Discussionmentioning
confidence: 87%
“…1991). There is a suggestion from some studies that patients who undergo orchipexy before the age of 10 years have a relatively low risk of developing tumours compared with those who undergo correction later (Martin et al, 1979;Strader et al, 1988). It is for these reasons that some authors have recommended orchidectomy for unilateral undescended testis when diagnosed after puberty (Ford et al, 1985).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The tumors are in 75–85% of cases seminomas, whereas after orchidopexy the proportion of seminomas is close to normal 50% [60, 61]. Thus, treatment appears to modify tumorigenesis, but it is still equivocal whether cancer risk can be reduced by early treatment of undescended testes [62, 63]. Testicular cancer is preceded in most cases by carcinoma in situ (CIS) [64]that may originate already during fetal development and may be caused by the same factors as cryptorchidism.…”
Section: Pathology In Maldescended Testesmentioning
confidence: 99%